Sustainable Performance Of Manufacturing Small And Medium Enterprises (Smes) In Malaysia: The Roles Of Sustainable Practices And Entrepreneurial Bricolage - Hassan, Nor Aishah (2021)
As a result of global economy, environmental and social catastrophes, businesses especially the entrepreneurs are seeking effective and efficient means to minimise the tremendous impacts. Although various theoretical foundations are beneficial in understanding the importance of sustainability, the sustainable performance of small-medium enterprises (SMEs) has yet to be explored. This research seeks to examine the drivers and outcome of sustainable practices to mitigate economic crisis, environment degradation, and social injustice. In particular, the individual (entrepreneurial leadership), organisational (sustainability culture), and institutional (government support implementation) level factors are presumed to drive the sustainable practices. These factors will in turn influence sustainable performance, and hence demonstrating the contingent role of entrepreneurial bricolage. Drawing on RBV and effectuation theory, a theoretical framework had been developed and analysed using 146 respondents among Malaysian manufacturing SMEs. An analytical method called Partial Least Squares (PLS) using SmartPLS software version 3.2.8 had been employed. The findings reveal that entrepreneurial leadership and sustainability culture are the key drivers of sustainable practices. Meanwhile, government support implementation is found to be not a significant factor that influences the practices. Additionally, sustainable practices are discovered to have positive effect on economic, environmental and social performance.